Synthesis and Characterization of Tetrakis(4-oxo-piperidinium ethylene acetal) Bis Sulfate Hexahydrate - H. Marouani; M. Rzaigui; S. S. Al-Deyab (E-Journal of Chemistry)
Chemical preparation, x-ray characterization, IR spectroscopy and thermal analysis of a new sulfate (C7H12O2NH2)4(SO4)2.6H2O, are reported. The atomic arrangement can be described by layers formed by sulfate anions (SO -24) and water molecules connected by hydrogen bonds O-H…O. These inorganic layers are developed around ab planes at z = 0 and z = 1/2 and are interconnected by the H-bonds created by organic groups. All the hydrogen bonds, the Van der waals contacts and electrostatic interactions between the different entities give rise to a three-dimensional network in the structure and add stability to this compound. The thermal behaviour and the IR spectroscopic studies of this new sulfate are discussed.